Kartun dan Komik Strip untuk Mengajar Bahasa dan Kepekaan Lintas Budaya Mahasiswa BIPA dari Thailand - Puspita Dian Agustin (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The use of cartoons and comic strips in cross-cultural and language instruction has significant advantages for Thai students' learning abilities. This study aims to: (1) determine Thai students at Muhamadiyah University in Jember's level of Indonesian comprehension through the use of cartoon and comic strip learning materials; ( 2) Using cartoons and comic strips as educational tools to introduce Thai students at Muhamadiyah University of Jember to Indonesian culture; 3) Provide a description of the cartoon and comic strip formats utilized in this study; also (4) Portray the aftereffects of further developing language picking up utilizing animation and funny cartoon gaining media for understudies from Thailand at the Muhamadiyah College of Jember. Descriptive statistics and qualitative descriptive analysis methods were used to analyze the data. The study's findings assign a BIPA level to Thai students enrolled at Muhammadiyah University of Jember. Additionally, the trial's findings demonstrate a rise in Indonesian language proficiency and cross-cultural awareness.